Modelling policy alternatives toward managed aquifer recharge in the Fergana Valley, Central Asia - Karimov, A.A.; Mavlonov, A.; Miryusupov, F.; Gracheva, I.; Borisov, V.; Abdurahmanov, Botir (Informa UK Limited, 2012)
Storing flow of the Syrdarya River in the aquifers of the upstream Fergana Valley in winter and recovery of this water in summer is examined as a solution for competing demands between upstream hydropower and downstream irrigation. Modelling of the Isfara and Sokh aquifers suggests the potential of reducing the Syrdarya River flow to the Fergana Valley downstream by 540 Mm3 in winter and increasing it by 540 Mm3 in summer. Implementing the proposed strategy in only these two aquifers would cover over 25% of the summer water deficit in the Syrdarya River downstream.